2018
DOI: 10.1007/s10853-018-2029-6
|View full text |Cite
|
Sign up to set email alerts
|

The effect of thermomechanical controlled processing on recrystallisation and subsequent deformation-induced ferrite transformation textures in microalloyed steels

Abstract: The evolution of texture components for two experimental 0.06 wt% C steels, one containing 0.03 wt% Nb (Nb steel) and the second containing both 0.03 wt% Nb and 0.02 wt% Ti (Nb-Ti steel), was investigated following a new thermomechanical controlled process route, comprising first deformation, rapid reheat to 1200°C and final deformation to various strains. Typical deformation textures were observed after first deformation for both steels. Following subsequent reheating to 1200°C for various times, the recrysta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 47 publications
(51 reference statements)
1
4
0
Order By: Relevance
“…Compared to the HAZ at the steel side, Figure 10 shows that the steel pseudo-NZs at all the welding parameters had more orientations with more HAGBs resulting in higher hardness [44,45]. This is in accordance with the results obtained by Tutar et al [46] who found that the NZ had higher hardness than the HAZ.…”
Section: The Effect Of Microstructure and Texture On Mechanical Propesupporting
confidence: 85%
“…Compared to the HAZ at the steel side, Figure 10 shows that the steel pseudo-NZs at all the welding parameters had more orientations with more HAGBs resulting in higher hardness [44,45]. This is in accordance with the results obtained by Tutar et al [46] who found that the NZ had higher hardness than the HAZ.…”
Section: The Effect Of Microstructure and Texture On Mechanical Propesupporting
confidence: 85%
“…The first observations of the dynamic transformation were reported in the patent registered in the 1980s [1], who performed large deformations in common C-Mn steels at approximately the Ar 3 temperature and then rapidly quenched, the final microstructure consisted of 70% or more of equiaxed ferrite grains with a size of 4 µm or less. In later works [2][3][4][5][6][7][8], the dynamic transformation was also observed at temperatures above the Ae 3 in plain carbon steels, the combination of large strains and multiple passes conducted to ultrafine grains of ferrite of around 2 µm. Extensive research has been carried out after the pioneering work of Yada and co-workers and numerous papers have been published mainly in the last two decades.…”
Section: Introductionmentioning
confidence: 95%
“…One of the most polemic topics has been the transformation mechanism of the dynamic ferrite, at least four different approaches [4][5][6][7][8][9][10][11][12][13][14][15] can be found in the literature attempting to explain the transformation path. One of the most accepted interpretations of the transformation mechanisms was proposed by [16], who carried out torsion tests above the Ae 3 temperature at strains from 0.5 to 2 in a steel containing 0.09%C-1.3%Mn-0.02%Si-0.036%Nb.…”
Section: Introductionmentioning
confidence: 99%
“…The outstanding properties of high‐strength low‐alloy (HSLA) steels such as high strength besides the suitable ductility and good weldability [ 4,5 ] lead them to be considered as the CT steel alloy. [ 2 ] The improvement in mechanical properties of this kind of steel can be achieved by optimizing processing parameters of different steps in the controlled rolling process, including reheating (soaking time and temperature), [ 6,7 ] rough rolling (reduction and temperature), [ 7–9 ] finish rolling (interpass time, thickness reduction, and temperature), [ 6,10–12 ] cooling (rate), [ 13–18 ] and coiling (temperature), [ 14,19,20 ] to achieve. In other words, to obtain fine‐grained ferrite, it is required to control the microstructural evolution during the thermomechanical treatment.…”
Section: Introductionmentioning
confidence: 99%
“…[ 25 ] The thermomechanical processing not only influences the microstructure evolutions, but also has a significant impact on the final texture, which makes it the subject of several research works. [ 8,11,26,27 ]…”
Section: Introductionmentioning
confidence: 99%